Structure-directed fabrication of ultrathin carbon nanosheets from layered metal salts: A separation and supercapacitor study. (November 2018) - Lyu, Hongliang; Zhu, Jikui; Zhou, Bihang; Cao, Haifei; Duan, Jingui; Chen, Lingyun; Jin, Wanqin; Xu, Qiang
Abstract: Ultra-thin carbon nanosheets showed specific and promising applications in energy conversions and mass transfers. Inspired by the idea of structure-directed formation, we report a catalyst-free, self-templated, eco-friendly, controllable and facile method for the preparation of high porous and ultrathin two dimensional carbon materials via in-situ thermal transformation of crystalline and layered metal-salt. The conversion mechanism was clearly validated, while the crystallization degree of graphitic carbon of series of nanosheets was systemically tuned. The hierarchical pore system enables the carbon nanosheets to show the N2 gas uptake up to 1780 cm 3 g −1 and pore volume to 2.7 cm 3 g −1 . With in-situ generated carboxylate and singly-bonded oxygen, the C-600 showed highest C3 H6 /C2 H4 gas selectivity (16.0) among all porous materials. More importantly, complete removal of C3 H6 from its C2 H4 mixture was confirmed by breakthrough experiments under flowing condition at ambient temperature. As well, due to the higher surface area, the symmetric supercapacitor device that assembled from C-600 showed excellent cycling durability (98.3%) with energy density of 18.39 Wh·kg −1 during ultrafast charging/discharging 10000 cycles. Graphical abstract: Image 1